DIPLOMASI PUBLIK PELAKU SINEMA INDONESIA DI FESTIVAL FILM CANNES KE-78 TAHUN 2025 - Putri Indah Syukriyah; Laksamana Zulfikar Satria Decca Harits; Mochammad Bahrul Alam Syah; Muhammad Indrawan Jatmika (Journal Publicuho, 2025)
The Cannes Film Festival, which began in 1949, is now entering its 78th edition in 2025. The Indonesian government, through the Ministry of Culture, held a Media Briefing for the Indonesian delegation at the Marché du Film as a form of recognition of film industry players as actors of public diplomacy. This study explains that participation in international festivals is one of the efforts of public diplomacy, and the public diplomacy efforts carried out by the Indonesian government as a state actor and the Indonesian film industry players at the Cannes Film Festival 2025 as non-state actors are analysed using Mark Leonard’s three-dimensional theory of public diplomacy. This research is analysed using a descriptive research method and a qualitative approach, employing secondary data. The results of this study show that the Indonesian government and Indonesian film industry players have conducted public diplomacy through news management, strategic communication, and relationship building.